A Multiple Stimuli‐Sensitive Low‐Molecular‐Weight Gel with an Aggregate‐Induced Emission Effect for Sol–Gel Transition Detection. Issue 6 (19th June 2018) - Wang, Hao; Liu, Qihong; Hu, Yalong; Liu, Miaochang; Huang, Xiaobo; Gao, Wenxia; Wu, Huayue
Abstract: A low‐molecular‐weight gel (LMWG) with a hydrazone moiety and an aggregate‐induced emission (AIE) unit was fabricated; the self‐assembly and disassembly of the LMWG under different stimuli conditions were studied. The LMWG exhibited multiple stimuli sensitivity with temperature, light, ions, and ionic strength. The hydrazone was integrated into the gelator to act as ion sensing sites and hydrogen bond donor groups to fulfil the task of ion recognition of Ni 2+, BH4 −, and OH −, as well as ion‐controlled reversible sol–gel recovery by adding H + for deprotonation; it also broke under UV irradiation to evoke light‐sensitivity. In addition, the sol–gel transition of the gel was detected by the AIE effect. The research provided an effective strategy in fabricating multiple stimuli‐sensitive LMWGs for potential biomedical applications. Abstract : Quick response : A multiple stimuli‐responsive low‐molecular‐weight gel with aggregate‐induced emission to detect a sol–gel transition exhibits light/heat/ion responses and ion‐controlled sol–gel recovery.